Birth of a Live Cria After Transfer of a Vitrified-Warmed Alpaca (Vicugna pacos) Preimplantation Embryo - Lutz, Jennifer C.; Johnson, Susan L.; Duprey, Kimberly J.; Taylor, Paul J.; Vivanco-Mackie, Henry William; Ponce-Salazar, Daniel; Miguel-Gonzales, Marlene; Youngs, Curtis R. (Frontiers in Veterinary Science, 2020)
The alpaca (Vicugna pacos) is an important species for the production of fiber and food. Genetic improvement programs for alpacas have been hindered, however, by the lack of field-practical techniques for artificial insemination and embryo transfer. In particular, successful techniques for the cryopreservation of alpaca preimplantation embryos have not been reported previously. The objective of this study was to develop an efficacious technique for cryopreservation of alpaca preimplantation embryos. Four naturally cycling non-superovulated Huacaya females serving as embryo donors were mated to males of proven fertility. Donors received 30 µg of gonadorelin at the time of breeding, and embryos were non-surgically recovered seven days after mating. Recovered embryos (n=4) were placed individually through a series of three vitrification solution (VS1: 1.4 M glycerol; VS2: 1.4 M glycerol + 3.6 M ethylene glycol; VS3: 3.4 M glycerol + 4.6 M ethylene glycol) before loading into an open-pulled straw (OPS) and plunging directly into liquid nitrogen for storage. At warming, each individual embryo was sequentially placed through warming solutions (WS1: 0.5 M galactose; WS2: 0.25 M galactose), and warmed embryos were incubated at 37°C in 5% CO2 in humidified air for 21 hours in 1 ml Syngro® holding medium supplemented with 10% (v/v) alpaca serum. Embryos whose diameter increased during culture (n=2) were transferred individually into synchronous recipients, whereas embryos that did not grow (n=2) were transferred together into a single recipient. Pregnancy was detected ultrasonographically 29 days post-transfer, and on November 13, 2019 the one pregnant recipient delivered what is believed to be the world’s first cria produced from a vitrified-warmed alpaca embryo.